Anaerobic contribution to the time to exhaustion at the minimal exercise intensity at which maximal oxygen uptake occurs in elite cyclists, kayakists and swimmers - Faina, M.; Squadrone, R.; DeAngelis, M.; Koralsztein, J. P.; DalMonte, A. (European Journal of Applied Physiology, 1997)
The data would suggest that the contribution of anaerobic processes during exercise performed at I VO2max (minimal exercise intensity at which maximal oxygen uptake occurs) should not be ignored when tlim is used as a supplementary parameter to evaluate specific adaptation of athletes.